Methodological recommendations for choreographic training of young acrobats - Shelgacheva A.M.; Bezhentseva L.M.; Kim D.S. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to provide a scientific basis for the efficacy of the application of the method of choreographic training for young acrobats during the initial training phase. Methods and structure of the study. Experimental work was carried out on the basis of MAU DO Youth Sports School No. 3 in Tomsk in the 2022/2023 academic year. The study involved 30 young acrobats training in initial training groups (15 in the experimental group - EG and 15 in the control group - CG). The training process in the CG was carried out in accordance with the current program, and in EG - according to a developed training methodology with the predominant use of choreographic training (ground gymnastics, Pilates and stretching) aimed at developing ballet step, eversion and lifting of the feet, strength of the leg muscles and flexibility of the spine. Results and conclusions. During the classes, the method of group work was used, which helped equip acrobats with ideas about the main points and lines of the hall, forms of formations and changes, development of the ability to «feel a partner» and navigate in space. The results of testing the special motor readiness of young acrobats from the EG and CG made it possible to establish reliable intergroup differences during the experiment in indicators assessing flexibility, jumping ability, and maintaining static balance.